Socket-based File Transfer System using AES-256 and OTP Authentication - Feni Widianti; Fauza Khair; Agung Mulyo Widodo; Eko Fajar Cahyadi (JURNAL INFOTEL, 2026)
The increasing risk of data interception during file transmission over open networks requires the development of secure communication systems. This study proposes a secure file transfer scheme that integrates the Advanced Encryption Standard (AES) with a 256-bit key and One-Time Password (OTP)-based authentication over socket programming. The system ensures that only verified users can transmit files by requiring password log-in and OTP verification via email. Upon successful authentication, files are encrypted using AES-256 before being transmitted over a TCP/IP socket connection. The implementation is carried out in Python using Visual Studio Code, with performance evaluated based on encryption time, transfer speed, and resistance to brute-force attacks. Various file types and sizes, including text, documents, images, audio, video, and compressed files, were tested to validate the robustness and efficiency of the system. The results show that the proposed system maintains high data integrity, enforces strong access control, and effectively resists unauthorized access, making it suitable for applications requiring secure file exchange.